ENTOMOLOGIA ROMANICA VOL.13/2008 - RAKOSY, Laszlo (2009)
The Bulletin of information is the periodical of the Romanian Lepidopterological Society with both scientific and informative content. The papers deal with systematics, faunistics, ecology, biology, zoogeography, behaviour of insects and insects’ conservation, as well as applied entomology. Categories are: Articles, General Notes, Faunistical Records, Technical Comments, Book Reviews, and Miscellaneous.